A constituição das formas identitárias dos professores/chefes de departamento dos cursos de licenciatura - Hobold, Márcia de Souza (2008)
Researches on teacher education (licensure) courses are important in order to know the context where the education of the prospective teachers has begun. The professionals who work in such courses have their own life stories, which are constituted by their personal, academic and professional experiences. In view of this factor, the current research has had as main purpose to understand how the identity forms of the teachers/heads of the licensure department are constituted in social and in work relations. The field of study of the current research was a communitarian university. At the first moment of data gathering, nine teachers/heads of department have been interviewed and they have told us the main activities developed in their day by day. A new interview was carried through later with the same teachers/heads, to better explore the aspects related to their professional /personal trajectory and to the performance of their function. Also four teacher educators, four former-students of licensure and the administrator directly connected to the heads of department have been interviewed. Finally, two teachers/heads have been interviewed with the objective to know the process of constitution of their identity forms in social and in work relations. These data had been complemented by document analysis of the institution. In the investigation plan there was the intention to follow the same steps of Claude Dubar (1997, 1998, 2005, 2006), in the studies carried out among French workers, in order to know how the life trajectories constitute the identity forms of the teachers/heads who act in licensure courses and their relation with the context of their work. Other authors have also constituted the theoretical structure of this thesis, amongst them: Andres (2001, 2006), Bauman (2004, 2005), Campos (2002), Candau (1988, 1997), Diniz- Pereira (2000), Elias (1994), Romanowski (2002) and Weber (2004). The narratives of teachers/heads of department on their familiar, academic and professional stories have been analyzed, as well as their leadership work. The transition of a teacher educator to a head of department was reported by many of them as difficult and even anguishing. It was not easy, for many of them, to take on a multiplicity of activities involved in the leadership function, for which they were not always felling prepared. They have had to restructure their knowledge, to develop abilities, and to answer to totally new situations and demands. The research has revealed that there is dynamicity in the (re)constitution of the identity forms, which is a process where the other has an important role. There is a permanent transaction between the identity for myself (I) and the identity for the other . The outcome of the research has corroborated the thesis that the configuration of the identity forms is directly tied to the situations of social and work relations, and that these can affect the daily actions of the heads of department of the licensure